Saxagliptin Attenuates Albuminuria by Inhibiting Podocyte Epithelial- to-Mesenchymal Transition via SDF-1α in Diabetic Nephropathy - Yun-peng Chang; Bei Sun; Zhe Han; Fei Han; Shao-lan Hu; Xiao-yu Li; Mei Xue; Yang Yang; Li Chen; Chun-jun Li; Li-ming Chen (Frontiers Media S.A., 2017)
The dipeptidyl peptidase-4 (DPP-4) inhibitor saxagliptin has been found to reduce progressive albuminuria, but the exact mechanism of inhibition is unclear. Podocyte epithelial-to-mesenchymal transition (EMT) has emerged as a potential pathway leading to proteinuria in diabetic nephropathy (DN). Stromal cell-derived factor-1α (SDF-1α), one of the substrates of DPP-4, can activate the protein kinase A pathway and subsequently inhibit its downstream effector, transforming growth factor-β1 (TGF-β1), which induces podocyte EMT. Thus, this study was designed to test the hypothesis that saxagliptin reduces progressive albuminuria by preventing podocyte EMT through inhibition of SDF-1α cleavage in DN. The results of a series of assays, including ELISA, western blotting, and immunochemistry/immunofluorescence, showed that saxagliptin treatment obviously ameliorated urinary microalbumin excretion and renal histological changes in high-fat diet/streptozotocin-induced diabetic rats. Furthermore, saxagliptin-treated diabetic rats presented with suppression of DPP-4 activity/protein expression accompanied by restoration of SDF-1α levels, which subsequently hindered NOX2 expression and podocyte EMT. In vitro, we consistently observed that saxagliptin significantly inhibited increased DPP-4 activity/expression, oxidative stress and podocyte EMT. Application of an SDF-1α receptor inhibitor (AMD3100) to cultured podocytes further confirmed the essential role of SDF-1α in podocyte EMT inhibition. In sum, we demonstrated for the first time that saxagliptin treatment plays an essential role in ameliorating progressive DN by preventing podocyte EMT through a SDF-1α-related pathway, suggesting that saxagliptin could offer renoprotection and that SDF-1α might be a potential therapeutic target for DN.